2020
DOI: 10.21203/rs.3.rs-29774/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The efficacy and safety of compound glycyrrhizin combined with desloratadine in the treatment of chronic urticaria: protocol for a systematic review of randomized controlled trials

Abstract: Background: Chronic urticaria (CU) is a common skin disease characterized by a short-term (<24 hours) spontaneous skin rash (urticaria) with or without angioedema that lasts longer than 6 weeks. CU is not life-threatening but has been shown to have a significant impact on the physical and mental health of patients. Because of chronic itching or physical discomfort in patients with CU, symptoms such as the repeated occurrence of red, swollen, itchy, anxiety, insomnia, and psychological stress are prone to oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Although long-term use of glycyrrhizin can cause electrolyte metabolism abnormalities, glycyrrhizinate containing glycine can be combined with L-cysteine hydrochloride to inhibit or reduce electrolyte metabolism disorders (Grob et al 2005). In addition, compound glycyrrhizin can improve the level of CD4þ T cells, reduce the level of CD8þ T cells, inhibit the release of arachidonic acid, and reduce leukotrienes (Wang 2016). Desloratadine in combination with compound glycyrrhizin can produce effects on different aspects of this disease, forming synergetic and complementary advantages in immune regulation and antiallergy, prolong the time of drug action, reduce the sensitivity of the body, enhance the clinical efficacy and reduce the recurrence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although long-term use of glycyrrhizin can cause electrolyte metabolism abnormalities, glycyrrhizinate containing glycine can be combined with L-cysteine hydrochloride to inhibit or reduce electrolyte metabolism disorders (Grob et al 2005). In addition, compound glycyrrhizin can improve the level of CD4þ T cells, reduce the level of CD8þ T cells, inhibit the release of arachidonic acid, and reduce leukotrienes (Wang 2016). Desloratadine in combination with compound glycyrrhizin can produce effects on different aspects of this disease, forming synergetic and complementary advantages in immune regulation and antiallergy, prolong the time of drug action, reduce the sensitivity of the body, enhance the clinical efficacy and reduce the recurrence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, both showed a low rate of AEs. In addition to common AEs of conventional therapy such as pruritus, erythema or papule, pseudoaldosteronism should be a specific adverse event of CG, 2 studies found CG might increase blood pressure, [44,57] 9 studies cause edema including lower feet edema, eyelids edema or facial edema, [29,3 1,34,36,38,40,44,48,57] and 2 studies found hypokalemia. [47,52] Patients with hypertension or cardiovascular disease should be cautious in receiving CG.…”
Section: Repigmentationmentioning
confidence: 99%
“…All studies were randomized controlled, but only eleven reported generation of random sequence and were evaluated as low risk. [29][30][31]36,41,42,44,45,57,60,61] All studies were classified as low-risk about selective reporting, incomplete outcome, other bias. All were judged as high risk in terms of performance bias since the lack of blinding of participants and personnel.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies [19,21,24,27,33,34,[36][37][38]41] reported methods of randomizing participants by using random number tables, which were considered low risk of bias; 13 trials mentioned randomization but did not explain the randomization method in detailed [17,18,20,23,25,26,28,30,31,35,39,40,42]; these were considered unclear risk of bias; and 3 trials [29,32,43] were grouped by treatment approach and one study [22] by visit sequence; the four studies were identifed as high-risk bias. None of the studies mentioned blindness and allocation hiding, which were considered unclear risk of bias.…”
Section: Risk Of Bias In Included Trialsmentioning
confidence: 99%